Delineation Of Padmini With A New Wave: Against The Social Customs By Girish Karnad - Sk.Rehena, Dr. Rama Devi Amara (International Journal of Advanced Science and Technology, 2020)
Indian women have to effort a lot in order to acquire their rights and getting the things done in the male-dominated, patriarchal society, which hardly gives any space in all aspects for them. The plight of women has become the subject matter for many writers who have depicted women as the secondary object, but Girish Karnad, the Gnanapeeth Awardee and with feminist ideologies tend him to project some of his women characters with domination, supremacy and revolt against the social customs and traditions. Padmini from Hayavadana is an abrupt example for all the above-mentioned features. The present paper focuses on how Padmini was successful in breaking the shackles of the male-dominated society for satisfying the psychological limits imposed by nature on her. Padmini was shown as against the traditions however she became an idle woman by performing sati at the end.